Between-assay variability of faecal calprotectin enzyme-linked immunosorbent assay kits. (January 2013) - Whitehead, S J; French, J; Brookes, M J; Ford, C; Gama, R
Background: Faecal calprotectin (f-Cp), a marker of intestinal inflammation, can be used to distinguish between functional and organic bowel disease. F-Cp, following extraction, is commonly quantified using enzyme-linked immunosorbent assays (ELISAs) but there are no data comparing the different f-Cp assays or sample extraction devices. We, therefore, evaluated and compared the performance of the Immunodiagnostik, Bühlmann and Eurospital f-Cp ELISA assays as well as the Roche, Immunodiagnostik and ScheBo Biotech commercial faecal extraction devices. We also briefly report results from a pilot f-Cp external quality assurance (EQA) scheme. Methods: Imprecision, linearity, recovery, drift and limit of quantitation of the f-Cp assays were evaluated and between-assay variability assessed. The three commercial sample extraction devices were compared with the manual weighing method. Four faecal samples were distributed as part of a pilot EQA scheme to 15 laboratories using quantitative ELISA f-Cp assays. Results: The three f-Cp assays demonstrated adequate intra-/interbatch imprecision, linearity and recovery. The crosscomparison study and EQA data demonstrated that, for the same sample, the Bühlmann assay reports up to 3.8 times higher f-Cp concentrations than the Immunodiagnostik and Eurospital assays. On average, the commercial extraction devices led to a 7.8-28.1% under-recovery of f-Cp in comparison to the manual weighing method. Conclusions: Laboratories should be aware of the lack of the assay standardization, as demonstrated by the between-assay variability. A comparison between f-Cp concentrations reported by these assays and clinical markers of disease severity is required in order to determine their diagnostic accuracy. The EQA scheme represents the first available programme for f-Cp.